Exploring the Influence of Sayyid Ahmad Khan's Thought on the Advancement of Islamic Education in India - Wani, Nasir Hassan; Rahman, Ikhwan; Amarullah, M. Faruk (Khalifa Journal of Islamic Education, 2023)
Sir Sayyid Ahmad Khan was an Indian Muslim intellectual known for his modernist views and often labeled a secularist due to his inclination toward rationalism and naturalism. In addition to being a political activist who played a role in the creation of Pakistan, he was also a prominent thinker and reformer in Islamic education in India. One of his key ideas was to integrate Western modern scientific concepts with Islamic studies. This integrated educational system became one of the most influential models in the Muslim world and is still widely adopted by contemporary Islamic educational institutions, each with its own variations. The model aims not only to produce Muslim intellectuals who master modern sciences but also to cultivate individuals with strong Islamic spirituality. This study aims to analyze Sayyid Ahmad Khan’s educational thought and its influence on the development of Islamic education in India. It employs a qualitative approach using a library research method and content analysis technique. The data were obtained from Sayyid Ahmad Khan’s works and relevant secondary literature, then analyzed to identify the main themes in his thought and their impact on the Islamic education system. The findings indicate that Sayyid Ahmad Khan’s educational ideas contributed significantly to the modernization of Islamic education through the integration of religious and modern sciences. However, this system has also faced criticism for insufficiently filtering the values of secularism, positivism, and materialism from the Western paradigm, potentially producing Muslim intellectuals who are scientifically advanced but spiritually fragile.